2017
DOI: 10.1093/ejo/cjx013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating low-level laser therapy effect on reducing orthodontic pain using two laser energy values: a split-mouth randomized placebo-controlled trial

Abstract: No funding to be declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
2
24
0
5
Order By: Relevance
“…The main finding of the study was that the mini-implants irradiated with a 635-nm diode laser at 20 J/cm 2 accounted to significantly greater secondary stability (after three days, one and two months) in contrast to non-irradiated side. Furthermore, a similar score of pain level was recorded on both sides of the maxilla, which agrees with findings of other randomized clinical split-mouth study concerning the effect of the application of low-level laser with 4-Joule or 16-Joule energy on pain reduction following elastomeric separators placement [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main finding of the study was that the mini-implants irradiated with a 635-nm diode laser at 20 J/cm 2 accounted to significantly greater secondary stability (after three days, one and two months) in contrast to non-irradiated side. Furthermore, a similar score of pain level was recorded on both sides of the maxilla, which agrees with findings of other randomized clinical split-mouth study concerning the effect of the application of low-level laser with 4-Joule or 16-Joule energy on pain reduction following elastomeric separators placement [9].…”
Section: Discussionsupporting
confidence: 90%
“…In implant dentistry and mini-implant assisted orthodontics, a sufficient process of measuring of implant's stability, and bone density is essential [6]. Because the removal torque method and histomorphometric analysis measurements are invasive techniques [9], Periotest and resonance frequency analysis (RFA) are more frequently used to assess implant stability [6,7]. One of the most common tools for assessing primary stability is Periotest (Medzintechnik Gulden e K, Modautal, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Of a total of 20 studies, 13 presented high risk of bias [ 9 , 23 , 24 , 26 , 28 – 30 , 32 , 34 , 36 38 , 40 ], five presented unclear risk [ 25 , 31 , 33 , 35 , 39 ], and two presented low risk [ 22 , 27 ]. “Blinding of personnel” was the principal risk of bias observed in studies, with ten studies where the operators were not blinded [ 9 , 23 , 26 , 28 – 30 , 34 , 37 , 38 , 40 ]; another four studies stated that the operators were blinded but gave no details of how this was done [ 31 – 33 , 36 ]. Although only randomized studies were included, it was observed that two studies did not carry out “random sequence generation” correctly [ 24 , 32 ], and five studies did not describe how the randomization sequence was generated [ 9 , 29 , 33 , 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although only randomized studies were included, it was observed that two studies did not carry out “random sequence generation” correctly [ 24 , 32 ], and five studies did not describe how the randomization sequence was generated [ 9 , 29 , 33 , 36 , 40 ]. Only three studies declared consistently how “allocation concealment” was done [ 22 , 25 , 27 ]; in three studies, the allocations could be predicted [ 23 , 24 , 32 ]; in one study, the authors declared that the sequence was concealed but gave no information on how the “allocation concealment” was effected [ 30 ], and the other studies did not offer sufficient information to judge the concealment of the randomization sequence. “Blinding of participants” and “blinding of outcome” were carried out in all studies except one [ 34 ], in which the authors declared that blinding was impossible due to the different pain management approaches employed in their study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation